Ionic conductivity studies on epoxy natural rubber-based polymer electrolytes for electrochemical system / Annie Maria Mahat - Mahat, Annie Maria (2006)
Epoxy natural rubber-based-50 (ENR-50) acted as a polymer host, lithium perchlorate (LiC104) as the doping salt, tetra hydrofuran (THF) as the solvent, poly carbonate (PC) as the plasticizer were used in this research project. The ENR-50 salt complexes and PC were prepared by solution cast technique. The electrical conductivities of all samples were measured by using the electrochemical impedance spectroscopy (EIS) at ambient and elevated temperature (303 K-373 K). From the EIS, true bulk resistance of each samples obtained from the complex impedance plot in the frequency range of 100 Hz-1 MHz were used to calculate the samples' conductivities. The highest conductivity was 8.55 x 10"5 Son"1 at 30 wt% salt for non-plasticized samples, while 2.2 x 10"4 Son"1 at 30 wt% PC for plasticized samples. The temperature dependence studies show that the samples obey the Arrhenius rule which indicate the conductivities were thermally assisted.